Comparative Efficacy of 2 L Polyethylene Glycol Alone or With Ascorbic Acid vs. 4 L Polyethylene Glycol for Colonoscopy: A Systematic Review and Network Meta-Analysis of 12 Randomized Controlled Trials - Tian, Xu; Shi, Bing; Chen, Hui; Liu, Xiao-Ling; Tang, Rong-Ying; Pi, Yuan-Ping; Chen, Wei-Qing (Frontiers in Medicine, 2019)
Background: Colonoscopy remains a standard method for early detecting and treating gastrointestinal lesions, however the quality of bowel preparation is the prerequisite of efficacy and safety of this process. Polyethylene glycol (PEG)-based bowel preparation regime has been the first recommendation before colonoscopy, but it is still unknown which regime is the optimal option. Aim: The objective of this network meta-analysis is to determine the efficacy and safety of 2L PEG alone or with ascorbic acid (Asc) compared with 4L PEG for bowel preparation before colonoscopy. Methods: Two independent investigators searched and screened potential records, abstracted essential information, and appraised risk of bias of individual study accordingly. Then, we adopted RevMan 5.3, Stata 14.0, and WinBUGS 1.4 software to perform all statistical analyses. The surface under the cumulative ranking curve (SCURA) was used to rank all regimes. Results: Twelve studies involving 4106 patients were analyzed finally. Pooled results indicated an improved bowel preparation efficacy in 2L PEG plus ascorbic acid with split-dose regime rather than in 2L PEG plus ascorbic acid (OR, 0.25; 95% CI, 0.18-0.36), 4L PEG with split dose (OR, 3.18; 95% CI, 2.17-4.66) and 4L PEG (OR, 4.53; 95% CI, 3.07-6.67) regimes, which was confirmed by network meta-analyses; a better compliance in 2L PEG plus Asc with split dose (OR, 3.08; 95% CI, 1.51-6.30) and 4L PEG with split dose (OR, 0.43; 95% CI, 0.22-0.82) regime rather than in 4L PEG regime, but network meta-analyses generated inconsistency results; a higher preference in 2L PEG plus Asc with split dose regime rather than in 4L PEG split dose (OR, 2.24; 95% CI, 1.02-4.90), which were not supported by network meta-analyses; no statistically significant difference when all regimes compared with each other in terms of adverse events. Conclusions: As for bowel preparation before colonoscopy, 2L PEG ascorbic acid with split dose should be optimally prescribed. Further studies comparing 2L PEG with 4L PEG, 4L PEG with split dose, and 2L PEG plus Asc with split dose respectively are warranted.